Pengaruh Kampanye Public Relations #SegarTanpaKhawatir di Instagram terhadap Brand Awareness Esteh Indonesia - Farisa Dea; Ratih Hasanah Sudrajat; Haris Annisari Indah Nur Rochimah (Universitas Batanghari Jambi, 2023)
The circulation of the issue of sugar in Esteh Indonesia's drinks requires it to move quickly to present the latest innovations, namely the sugar level or level of sweetness in drinks that can be adjusted to its consumers. This innovation was introduced through the #SegarTanpaKhawatir public relations campaign which was uploaded on Esteh Indonesia's Instagram account. The purpose of this study was to measure how much influence the #SegarTanpaKhawatir public relations campaign on Instagram had on Esteh Indonesia's brand awareness. This study uses a descriptive quantitative approach with data collection techniques through online questionnaires. The sample technique used was purposive sampling and produced 400 respondents who were a group of young adults with an age range of 15-29 years and were aware of the #SegarTanpaKhawatir public relations campaign on Instagram. The results of the study show that the #SegarTanpaKhawatir public relations campaign has a positive influence on Esteh Indonesia's brand awareness with a moderate level of relationship. This study found that Esteh Indonesia's brand awareness was still at the level of brand recall. So, through these findings, it is hoped that Esteh Indonesia can further develop its marketing activities so that it becomes a top of mind product in its category.